PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK ME NINGKATKAN HASIL BELAJAR IPASISWA KELAS V SDN 033 SINTONG KECAMATAN TANAH PUTIH - Esi Erpika; Mahmud Alfusari; Lazim.N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem this reseach is the students achievement of sains fiveh graders studies still low with an average value of 65 and minimum completeness criteri (KKM) sains studies is 70. Between students, amounting to20 people only 8 students who acieve classical KKM with 40%. This research is Classroom Action Research (Car), which aims to improve the student achievement of Sains studies class V at SDN 033 Sintong with implementation Inquiry learning model. Formulation of the problem : Is the implementation Guided Inquiri lerning model can improve students achievement of Sains studies at SDN 033 Sintong. Subjects were students of SDN 033 Sintong, totaling 20 people who use the data source. The data collection achivement. This thesis presents the results obtained eachdai before the action an improve in base score cycle with the average being 65. In the first cycle improved an average of 69 and an improved in the second with an average of 82,50. Action of the teacher in the learning prosess at the cycle I75,00% improved 91,67% in cycle II. Results of data analisys of students activitiesin the I cycle is 66,67% improved 95,83%. Results in the class V at SDN 033 Sintong that the implementation of inquiry learning model can improved the student achievement of Sains studies at fiveh graders SDN 033 Sintong..Key Word : Guided Inguiry Learning Model